MAKIAN DALAM BAHASA (DIALEK) MELAYU KUPANG - Djawa, Alex; Djuli, Labu (Jurnal Lazuardi, 2024)
The dirty word is usually done by people closest to them, such as parents to children, children to parents, between children and children, or between friends and friends. Dirty word occurs because of annoyance, hatred and anger. The dirty word that are often used in Kupang Malay are in the form of words, phrases and clauses. Dirty words in the form of words such as: tolo, puki, anjing(dog), babi(pig). Re-form words, such as: anjing-anjing(dogs), babi-babi(pigs), kode (monkey). In the form of compound words, such as: puki mai, cuki mai, lele hanak. In the form of phrases, such as: dasar lonte (you slut), dasar pancuri (your a thief), dasar tartau diri. Characters that are different from Indonesian, such as: lu pung mai, lu pung no'o, lu pung tolo boa. In the form of clauses, such as: lu su gila, basong su gila, parampuan bagatal, parampuan lonte, mai pung puki lobang, and basong pung panta lobang.